Applying Response to Intervention to Identify Learning Disabilities in Students With Visual Impairments. (September 2015) - Jones, Beth A.; Smith, Heather Haynes; Hensley-Maloney, Lauren; Gansle, Kristin A.
When visual impairments (VI) and learning disabilities (LD) coexist, it is common for one (i.e., typically LD) to go unidentified. Some school districts may be reluctant to identify students with both VI and LD, potentially causing students to miss out on much-needed services. Child study teams can find support to address this dual diagnosis using a response to intervention (RTI) framework. This article provides guidance and tools for using an RTI framework in the accurate identification of LD in students with VI.